Assignment of local coordinate systems and methods to calculate tibiotalar and subtalar kinematics: A systematic review - Lenz, A.; Strobel, M. A.; Anderson, A. M.; Fial, A. V.; MacWilliams, B. A.; Krzak, J. J.; Kruger, K. M. (Journal of Biomechanics, 2021)
The introduction of biplane fluoroscopy has created the ability to evaluate in vivo motion, enabling six degree-of-freedom measurement of the tibiotalar and subtalar joints. Although the International Society of Biomechanics defines a standard method of assigning local coordinate systems for the ankle joint complex, standards for the tibiotalar and subtalar joints are lacking. The objective of this systematic review was to summarize and appraise the existing literature that (1) defined coordinate systems for the tibia, talus, and/or calcaneus or (2) assigned kinematic definitions for the tibiotalar and/or subtalar joints. A systematic literature search was developed with search results limited to English Language from 2006 through 2020. Articles were screened by two independent reviewers based on title and abstract. Methodological quality was evaluated using a modified assessment tool. Following screening, 52 articles were identified as having met inclusion criteria. Methodological assessment of these articles varied in quality from 61 to 97. Included articles adopted primary methods for defining coordinate systems that included: (1) anatomical coordinate system (ACS) based on individual bone landmarks and/or geometric shapes, (2) orthogonal principal axes, and (3) interactive closest point (ICP) registration. Common methods for calculating kinematics included: (1) joint coordinate system (JCS) to calculate rotation and translation, (2) Cardan/Euler sequences, and (3) inclination and deviation angles for helical angles. The methods each have strengths and weaknesses. This summarized knowledge should provide the basis for the foot and ankle biomechanics community to create an accepted standard for calculating and reporting tibiotalar and subtalar kinematics.